1982
DOI: 10.1002/pol.1982.170200111
|View full text |Cite
|
Sign up to set email alerts
|

Polyureas from carbon dioxide and diamines by means of triphenyl phosphite and pyridine hydrochloride

Abstract: SynopsisThe reaction of carbon dioxide with aniline using triphenyl phosphite in pyridine is greatly facilitated by the addition of hydrochlorides of tertiary amines such as pyridine and triethylamine, and has been successfully applied to the preparation of polyureas of high molecular weight from carbon dioxide and aromatic diamines. The presence of a catalytic amount of pyridine hydrochloride significantly increased the inherent viscosity of the resulting polymers, the highest value being obtained with about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Structure of copolymer epoxide-CO 2 IR analyses were made for the synthesized copolymer. It was found that there were characteristic absorption peaks for carbonyl and COO of the carbonate group for every polymer around 1750 and 1260 cm…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structure of copolymer epoxide-CO 2 IR analyses were made for the synthesized copolymer. It was found that there were characteristic absorption peaks for carbonyl and COO of the carbonate group for every polymer around 1750 and 1260 cm…”
Section: Resultsmentioning
confidence: 99%
“…1 Over the past several years, large advances have been made in the development of CO 2 for polymer synthesis applications. [2][3][4][5][6][7][8][9][10] It is a new and important research area in C1 chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Recently, a new route was reported for the nonisocyanate polyurea synthesis by using dicarbamates and diamines as monomers. [8e,10a-c,17] Polyurea was also synthesized via addition of CO 2 to diamine compounds under catalytic conditions, using triphenyl phosphate, [18] ethylene chlorophosphite, [19] ionic liquid., [10d,20] and inorganic base [17c] as catalysts. [16] Our group synthesized a series of polyureas using CO 2 and diamine without catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Another polymerization scheme towards aramids not requiring transformation of the diacid into the more expensive and difficult to handle diacyl chlorides is possible with the so-called condensing agents. The latter, being derived from phosphorus and sulfur containing compounds, activate the aromatic acid in situ during polymerization [12]. The reaction has not been utilized commercially because the costs of recovering and regenerating the condensing agents by far outweigh the cost advantage of using unmodified diacids.…”
Section: Synthesis Of Aramidsmentioning
confidence: 99%